2009
DOI: 10.7202/038554ar
|View full text |Cite
|
Sign up to set email alerts
|

National Culture and Union Membership

Abstract: Résumé de l'article La culture nationale et la syndicalisation : une approche culturelle et cognitive Voulant aller au-delà des perspectives normatives et régulatrices de la théorie néo-institutionnelle, cette étude se sert d'une perspective culturelle et cognitive pour étudier l'influence portée par les dimensions multiples d'une culture nationale sur la syndicalisation. Dans ce but, les structures culturelles ont été comparées en utilisant des données du World Values Survey qui ont été associés aux résultats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 69 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…Using micro-data files for 34 countries Blanchflower (2007) found that, prior to 2005, union density rates peaked in midlife maximizing in the mid to late 40s. 3 4 This U-shaped, or hump shaped, pattern was also found subsequently for Norway by Nergaard and Stokke (2007) and Posthuma (2009) in the World Values Survey, 1999-2002. Blanchflower found it made little difference whether controls were included, such as education, gender, race, occupation, location and so on; the probability of being a union member peaked in midlife.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Using micro-data files for 34 countries Blanchflower (2007) found that, prior to 2005, union density rates peaked in midlife maximizing in the mid to late 40s. 3 4 This U-shaped, or hump shaped, pattern was also found subsequently for Norway by Nergaard and Stokke (2007) and Posthuma (2009) in the World Values Survey, 1999-2002. Blanchflower found it made little difference whether controls were included, such as education, gender, race, occupation, location and so on; the probability of being a union member peaked in midlife.…”
Section: Introductionmentioning
confidence: 60%
“… The WVS sweeps are 19811989-19931999- 2009 (45,208) and 2017-2019 with # observations in parentheses.…”
mentioning
confidence: 99%
“…Using micro-data files for 34 countries Blanchflower (2007) found that, prior to 2005, union density rates peaked in midlife maximizing in the mid to late 40s. 3 4 This U-shaped, or hump shaped, pattern was also found subsequently for Norway by Nergaard and Stokke (2007) and Posthuma (2009) in the World Values Survey, 1999. Blanchflower found it made little difference whether controls were included, such as education, gender, race, occupation, location and so on; the probability of being a union member peaked in midlife.…”
Section: Introductionmentioning
confidence: 62%
“… The WVS sweeps are 19811989-19931999- 2009;2010-2014 (45,208) and2017-2019 (40,771) and all (202,976) with # observations in parentheses.…”
mentioning
confidence: 99%
“…By referring to cultural as well as institutional factors that might hint at a larger degree of risk aversion on the part of Japanese employees as opposed to U.S. employees, we do not only uncover one potential explanatory factor for the evolution of different types of tournaments in the two countries, but we also contribute to the body of literature on how cultural and institutional factors might reinforce each other (see e.g. Black, 2001or Posthuma 2009). In a final step of our paper we highlight the recent changes in the Japanese employment system and discuss in how far these recent trends might change future tournament structures in Japan.…”
Section: Introductionmentioning
confidence: 97%